Finding luck - Earhart, Kristin (Marguerite Henry's Misty Inn, 2016)
With the grand opening of their family's bed-and-breakfast approaching, Willa and Ben are tired of helping their parents get ready for the big day and would much rather be helping their Grandma Edna reunite a foal with its missing mother.